2008
DOI: 10.1016/j.pbb.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Low dose MK-801 reduces social investigation in mice

Abstract: To characterize MK-801’s effect on social behavior in mice, we examined adult male ICR mice for interaction with companion mice (juvenile male). Test mice were injected with either saline or MK-801 (0.1 mg/kg), and were tested 30 min later for their social behavior during a 5-min session. A second encounter took place 30 min later, with either a familiar companion mouse (the same as in the initial encounter) or a novel mouse. In saline controls, second encounter with a familiar companion mouse showed reduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
6
20
0
Order By: Relevance
“…Furthermore, SR−/− mice have many of the same brain morphological abnormalities observed in schizophrenia, such as reduced cortico-hippocampal volume, decreased dendritic spine density (Balu et al, 2012; Balu et al, 2013) and increased lateral ventricles (Puhl et al, 2015). Pharmacological NMDAR hypofunction models produce hyperlocomotion and stereotypy (Hoffman, 1992), as well as social withdrawal (Zou et al, 2008), behavioral abnormalities that are not observed in SR−/− mice (Basu et al, 2009; DeVito et al, 2011). Thus, the SR−/− mice exhibit a forebrain NMDA receptor hypofunction endophenotype with cortical neuronal atrophy associated with negative symptoms and cognitive but not with several behavioral abnormalities linked to psychosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SR−/− mice have many of the same brain morphological abnormalities observed in schizophrenia, such as reduced cortico-hippocampal volume, decreased dendritic spine density (Balu et al, 2012; Balu et al, 2013) and increased lateral ventricles (Puhl et al, 2015). Pharmacological NMDAR hypofunction models produce hyperlocomotion and stereotypy (Hoffman, 1992), as well as social withdrawal (Zou et al, 2008), behavioral abnormalities that are not observed in SR−/− mice (Basu et al, 2009; DeVito et al, 2011). Thus, the SR−/− mice exhibit a forebrain NMDA receptor hypofunction endophenotype with cortical neuronal atrophy associated with negative symptoms and cognitive but not with several behavioral abnormalities linked to psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NMDAR antagonists have been used as a tool to induce NMDAR hypofunction in experimental animals as a pharmacologic model of schizophrenia (Adell et al, 2012; Eyjolfsson et al, 2006; Javitt and Zukin, 1991; Wiescholleck and Manahan-Vaughan, 2013). These pharmacological models exhibit hyperlocomotion, stereotypies (Hoffman, 1992) and social withdrawal (Zou et al, 2008), as well as long-term potentiation (LTP) and learning deficits (Manahan-Vaughan et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…While not as well studied as social interaction, there have been several research studies analyzing impaired social recognition in animal models of schizophrenia. For example, acute treatment with MK-801 (0.1 mg/kg) produced diminished discriminative capabilities for a familiar versus novel conspecific in both male rats and mice (Zou et al, 2008). Additionally, pretreatment with clozapine (0.3–1 mg/kg), but not haloperidol (0.01–0.1 mg/kg), significantly attenuated the effects of MK-801 in male rats (Shimazaki et al, 2010).…”
Section: Social Interactionmentioning
confidence: 99%
“…Recent evidence has implicated NMDAR dysfunction in ASD (Carlson, 2012). Administration of NMDAR antagonists or NR1 deficiency induces ASD-like social deficits in mice (Zou et al, 2008). Shank2 or Shank3 -lacking mice exhibit impaired NMDAR-dependent synaptic plasticity along with ASD-related behaviors (Wang et al, 2011; Won et al, 2012; Kouser et al, 2013).…”
Section: Introductionmentioning
confidence: 99%